Investigating 6-3-5 Brainwritting Strategy on Students’ Writing Performance Using Narrative Text (A Classroom Action Research) - Lambertus Tibertius Beda Amasuba amasuba; Haryanto Atmowardoyo; Andi Anto Patak (International Journal of Language, Education, and Literature, 2024)
ABSTRACT This research investigates students' writing performance by applying the 6-3-5 brainwriting strategy to students. Of course, the aim of this research is to determine the effect of the 6-3-5 brainwriting strategy on the development of students' writing skills as well as students' perceptions of the strategies applied by fourth grade students at Menara St. Martinus Elementary School, Makassar. This research uses a mix-method design method which combines two qualitative and quantitative methods with design triangulation in the research. The research was conducted through a classroom action research approach, focusing on the qualitative and quantitative improvements in students' writing performance. The population of this study was all fourth-grade students, totaling 20 students. Researchers used several research instruments, namely observation paper and checklist, interview guidance and writing test. The results of this research show that students' writing skills improved in phase 1 and phase 2. This can be seen from the comparison of the scores obtained by students during the pre-test of 65.6 while the first post-test was 73.4 and the second post-test was 78.7. The comparison of the scores above shows significant development in students' writing abilities. In terms of students' perceptions of the strategy applied, based on the results of observations and interviews before and after implementing the strategy, this strategy is seen as a strategy that really helps students in creating ideas based on the objects displayed.